Repurposing Proteostasis-Modifying Drugs to Prevent or Treat Age-Related Dementia: A Systematic Review - Heard, Daniel S.; Tuttle, Camilla S. L.; Lautenschlager, Nicola T.; Maier, Andrea B. (Frontiers in Physiology, 2018)
Background: Dementia has a significant impact on quality of life of older individuals. Impaired proteostasis has been implicated as a potential cause of dementia, that can be therapeutically targeted to improve patient outcomes. This review aimed to collate all current evidence of the potential for targeting proteostasis with repurposed drugs as an intervention for age-related dementia and cognitive decline. Methods: PubMed, Web of Science and Embase databases were searched from inception until 4th July 2017 for studies published in English. Interventional studies of repurposed proteostasis-modifying drugs in Alzheimer’s disease (AD), Parkinson’s disease (PD), Lewy Body disease, vascular dementia and cognitive aging, in either animal models or humans with change in cognition as the outcome were included. The SYRCLE and Cochrane tools were used to assess risk of bias for included studies. Results: Overall 47 trials, 38 animal and 9 human, were isolated for inclusion in this review. Drugs tested in animals and humans included lithium, rapamycin, rifampicin, and tyrosine kinase inhibitors. Drugs tested only in animals included Macrophage and Granulocyte-Macrophage Colony Stimulating Factors, methylene blue, dantrolene, geranylgeranylacetone, minocycline and phenylbutyric acid. Lithium (n=10 animal, n=6 human) and rapamycin (n=12 animal, n=1 human) were the most studied proteostasis modifying drugs influencing cognition. Nine of ten animal studies of lithium showed a statistically significant benefit in Alzheimer’s models. Rapamycin demonstrated a significant benefit in models of vascular dementia, aging, and Alzheimer’s, but may not be effective in treating established Alzheimer’s pathology. Lithium and nilotinib had positive outcomes in human studies including Alzheimer’s and Parkinson’s patients respectively, while a human study of rifampicin in Alzheimer’s failed to demonstrate benefit. Microdose lithium showed a strongly significant benefit in both animals and humans. While the risk of bias was relatively low in human studies, the risk of bias in animal studies was largely unclear. Conclusion: Overall, the collective findings support the hypothesis that targeting proteostasis for treatment of dementia may be beneficial, and therefore future studies in humans with repurposed proteostasis modifying drugs are warranted. Larger human clinical trials focusing on safety, efficacy, tolerability and reproducibility are required to translate these therapeutics into clinical practice.